(untitled) (TAJ: Journal of Teachers Association, 2019)
Worldwide millions of women seek induced abortion. When successful and complete, it remains secret and if complicated gets highlighted. Hospital data represents a tip of the ice berg. It is an important cause of maternal morbidity and mortality but is preventable. This study was done to have a view to some socio-demographic aspects of induced abortion. This study was conducted from January 2012 to July 2012. Patients admitted with illegal induced abortion (N=50) were included in this study. Patients with spontaneous abortions were excluded. Data was collected using pre-designed data collection sheet and were expressed as actual number and percentage. Age range was 15-45 years with maximum incidence in 25-35 years. Peri-urban & rural area were the maximum habitat. Majority patients and their husbands were illiterate or only had primary level education. Most of them were housewives and majority of their husbands were day laborers or small-business holders. Most of their knowledge about different contraceptives was poor and knowledge of MR services was uncertain or none. 96% of their pregnancies were unwanted. Abortions were induced at local clinic, at own residences or at inducers’ residence. Methods of abortion induction were MR, drugs or herbal agents. Abortions were induced by nurse, respondents herself, ‘dai’ or by midwives; none by physician or well trained personnel. One (2%) patient died due to haemorrhage and sepsis. Rural, illiterate persons of our community with little or poor knowledge of family planning services are at risk of having unwanted pregnancy. And, poor knowledge regarding MR or related facilities, as well as legal restriction provokes them to induce abortions by poorly trained personnel and thereby endangering their lives. TAJ 2018; 31(2): 63-67